توظيف الطريقة المباشرة لتعليم مهارة الكلام لغير الناطقين بها بقسم اللغة العربية بالمدرسة الثانوية القادري الإسلامية بجمبر جاوى الشرقية - Elok Rufaiqoh; Muhammad Ainul Yakin; Muhammad Yunus (UIN Fatmawati Sukarno Bengkulu, 2020)
AbstractThe goal of this study was to evaluate the implementation in the Language Program at Madrasah Tsanawiyah Al-Qodiri Jember, East Java, of direct methods for learning speaker skills other than non-Arabic speakers. Using observation, interview and reporting methods, the approach used is a qualitative method. As for the outcomes of implementing the direct method for learning speaking abilities, this method contributes a great deal to Arabic speaking, especially in the development of a language environment, this method also gives students trust in this school environment.